Early to Mid-Holocene land use transitions in South Asia: A new archaeological synthesis of potential human impacts - Bates, J.; Morrison, K. D.; Madella, M.; Hill, A. C.; Whitehouse, N. J.; Abro, T.; Ajithprasad, P.; Anupama, K.; Casile, A.; Chandio, A.; Chatterjee, S.; Gangopadhyay, K.; et al. (PLOS ONE, 2025)
While it is clear that current human impact on the earth system is unprecedented in scope and scale, much less is known about the long-term histories of human land use and their effects on vegetation, carbon cycling, and other factors relevant to climate change. Current debates over the possible importance of human activities since the mid second millennium CE cannot be effectively resolved without evidence-based reconstructions of past land use and its consequences. The goal of the PAGES LandCover 6K working group is to reconstruct human land use and land cover over the past 12,000 years. In this paper, we present the first large-scale synthesis of archaeological evidence for human land use in South Asia at 12 and 6kya, a critical period for the transition to agriculture, arguably one of the land use transitions most consequential in terms of human impact on the Earth system. Perhaps the most important narrative we can pick out is that while there are some shifts in land use across these time windows, hunter-gatherer-fisher-foraging remained the dominant land use, and within this there was a mosaic of strategies exploiting diverse and complex landscapes and ecologies. This is not necessarily a new conclusion–it is not new to state that South Asia is comprised of many niches, but demonstrating the deep time history of how people have adapted to these and adapted them is an important step for modelling the impacts of human populations and thinking about their footprints in a longue-durée perspective. Despite the new development of food production between the early and mid-Holocene by overall area foraging life ways continued as the dominant land use practice into the 6kya time window. The development of agriculture and food production was not unimportant–it is the beginning of a land use that eventually comes to dominate the sub-continent, but at 6kya agriculture was restricted to specific contexts. Across 12kya to 6kya and different land uses, the use of mosaic ecologies, diverse strategies and the importance of water as a resource stand out as shared themes.